CWNA Certified Wireless Network Administrator Official Deluxe Study Guide Exam CWNA-106 - Coleman, David; Westcott, David (Sybex, 2015)
Complete CWNA-106 prep, with full coverage and hands-on practice CWNA Certified Wireless Network Administrator Deluxe Study Guide is your official study guide for the leading wireless certification program. Updated for the new CWNA-106 exam, this book provides coverage of all exam objectives, plus review questions and hands-on exercises that help you build your skills and your confidence before exam day. Start with a pre-assessment test to find out how much you already know, then fill in the gaps with detailed coverage of radio frequency technology, regulations and standards, protocols and devices, network implementation and security, RF site surveying, and much more. Sybex's interactive online learning environment and test bank gives you access to hundreds of questions and robust study tools, including chapter tests, practice exams, flashcards, a glossary of key terms, and bonus chapter material - all to help you prepare for and increase your chances of passing the exam the first time around. Find your starting point with a pre-assessment test Get up to speed on all CWNA-106 exam objectives Sharpen your practical skills with hands-on exercises Test your knowledge with practice exam questions Savvy candidates know that strategic prep is essential to first-time success, and CWNA Certified Wireless Network Administrator Deluxe Study Guide is your toolbox for building the next step in your wireless career.